Oral Feeding Practices in NICU Infants on CPAP or HFNC: A U.S. Cross-Sectional Survey - Koehler, Monica; Selvakumar, Shreyaashri; Viswanathan, Sreekanth (American Journal of Perinatology, 2025)
Coordination of sucking–swallowing–breathing matures at 32 to 34 weeks' gestation; early oral feeds risk aspiration, while delays may increase oral aversion and length of stay. Safety of feeding on high-flow nasal cannula (HFNC) or continuous positive airway pressure (CPAP) is uncertain, and practice variations are common. This study describes the U.S. neonatal intensive care unit (NICU) practices for oral feeding during HFNC/CPAP and decision criteria.National cross-sectional telephone survey (July 2024–February 2025) of key informants from level III and IV NICUs.Of 159 NICUs, 83.0% routinely permitted oral feeding on HFNC, 10.7% sometimes, and 6.3% never. Only 9.4% routinely allowed CPAP feeding, 7.5% sometimes, and 83.0% never. Units allowing CPAP feeding used stricter readiness criteria, continuous monitoring, and involved speech-language pathology/occupational therapy.Oral feeding on HFNC is common; CPAP feeding is rare and criteria-bound, with regional variation. Heterogeneity underscores the need for consensus guidance and trials evaluating CPAP feeding effects on feeding outcomes, length of stay, and neurodevelopment.
Keywords: oral feeding difficulty; CPAP; HFNC; preterm infants; NICU